Urban Sewage and Green Meadows: Berlin's Expansion to the South 1870–1920. Issue 2 (9th July 2014) - Gray, Marion W.
Abstract : On May 23, 1908, Frau Treppens, the proprietress of a Gasthaus near the agricultural estate Klein Ziethen contacted the governing council of Steglitz regarding an urgent concern about water damage. Steglitz was five kilometers south of Berlin's southern boundary; Klein Ziethen was twelve kilometers southeast of Steglitz. Writing on the advice of attorney Georg Hillman, Frau Treppens urgently inquired what the council was going to do about the water on her property, which had already caused "enormous damage." Like many other property owners near Klein Ziethen, she had been battling water in her basement; for some this had been going on for two years. Frau Treppens inquired what steps Steglitz was taking against Rixdorf, another rapidly growing suburb, located on Berlin's southeast perimeter sixteen kilometers from Klein Ziethen. Why was Frau Treppens turning to the officials of Steglitz, and why did she and her attorney assume that Steglitz and Rixdorf bore responsibility for her water-soaked cellar?